2010
DOI: 10.5897/ajb09.1253
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drought stress on the activity of acid phosphatase and its protective enzymes in pigweed leaves

Abstract: A model of drought was created on pigweed and the effects of drought stress on the activity of acid phosphatase and its protective enzymes were examined. The pot-cultured pigweeds were divided into 4 groups (ten plants per group) when they reached 6 leaves. (1) In the control group, the culture media contained 70 -85% of field moisture capacity, (2) In the second group, the mild drought stress group, the culture media contained 50 -60% of field moisture capacity, (3) The moderate drought stress group had a cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Fang et al (2008) have shown the enhancing effect of the lactose on cellulase production by Acremonium cellulolyticus. In a study by Sun et al (2010), Trihoderma species cultivated on apple pomace under SSF conditions produced the highest levels of cellulase when supplemented with lactose. In Acrophialophora nainiana also, the highest CMCase production was induced in the presence of lactose (Barros et al 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Fang et al (2008) have shown the enhancing effect of the lactose on cellulase production by Acremonium cellulolyticus. In a study by Sun et al (2010), Trihoderma species cultivated on apple pomace under SSF conditions produced the highest levels of cellulase when supplemented with lactose. In Acrophialophora nainiana also, the highest CMCase production was induced in the presence of lactose (Barros et al 2010).…”
Section: Resultsmentioning
confidence: 98%
“…Antioxidant enzymes play important roles in adaptation to stress conditions. SOD, POD, and CAT are protective enzymes in plants and they can be affected by light and cold stress (Gechev et al 2003), salinity (Rios-Gonzalez et al 2002;Misra & Gupta 2006), high temperature stress (Ali et al 2005;Almeselmani et al 2006), and drought stress (Sun et al 2010). The coordinated functions of antioxidant enzymes, such as SOD, CAT, and POD, facilitate ROS processing and Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton is one of the species with strong salt tolerance and is a pioneering crop in saline land. Previous studies have discussed the effects of salt on photosynthesis [4]- [7], antioxidants [8] [9], seed germination [10] [11], and cellular structure [12]. Moreover, cotton has been found to perceive and respond to various adversities, including salt stress.…”
Section: Introductionmentioning
confidence: 99%